Influence of Culture on Investment Decisions: A Cross-Sectional Study of Ghanaian Population - Bonna, Adu; Awobgo-Moah Amoah, Robert (Journal of Economics and Behavioral Studies, 2020)
Abstract: This study seeks to explore the influence of culture on the investment decisions of Ghanaians. It is motivated by the perception that Ghanaians show no enthusiasm for long-term investments or life insurance products. To explore this problem, we used a random sampling, quantitative cross-sectional technique to administer a set of questionnaires to a cross-section of 120 Ghanaians residing in the City of Columbus, Ohio, U.S.A. Hofstede’s five cultural dimensions were used as the theoretical framework to guide the study. The results showed that Ghanaians prefer short-duration risk-free investments to long-duration risky investments. Ghanaian investors are not aggressive in gathering and analyzing financial information before making investment decisions. Their investment decisions are influenced by others, intuition, comfort and security, and their belief systems, rather than rational analysis of information, and risk-reward relationships derived from financial models. The use of intuition and information passed on from relatives, family members and others in making investment decisions paves the way for cultural factors to influence investment decisions. We conclude that cultural values have significant influence on the investment decisions of Ghanaians. The study seeks to motivate investors to examine and broaden their cultural awareness to enable them to develop financial plans to achieve their investment goals. We recommend that to overcome negative cultural influence on investment decision making, financial education should be vigorously pursued to broaden financial literacy.